Better Be Ready! Evacuation Experiences During a Bushfire Emergency - Carina C. Anderson; Susan F. Rockloff; Lucinda P. Burton; Victoria R. Terry; Sally K. Jensen; Anne T. Nolan; Peter C. Terry (Fire)
This paper reports on research undertaken for the Building Resilience for Bushfire-Affected Communities in Noosa Shire project, funded by the Australian Government. Being evacuated from a home in the path of a bushfire can be traumatic. Therefore, it is important for evacuees to have safe places to stay, both physically and psychologically. Using a qualitative approach, we aimed to (a) understand the experiences of people who were displaced from their homes and sheltered at evacuation centres during the Noosa Shire bushfires and (b) understand what support is needed during disasters, such as bushfires, to help create positive experiences for future evacuees. Twelve participants displaced by bushfires in Noosa, Australia, in 2019 recalled their experiences in semi-structured interviews (conducted in 2022–2023). Inductive thematic analysis using NVivo 13 identified three themes that can inform government and public disaster preparation and response: planning, support, and communication. Findings from this study centred around building community resilience and offer valuable insights for organising disaster evacuation processes and evacuation centres on a broader scale. For individuals, it involves planning optimal evacuation routes, gathering necessary personal items, feeling safe and calm in evacuation centres, and receiving regular and accurate communication from authorities during disaster events.